Current state of radon concentration studies - Еримбетова, Д; Степаненко, В; Видергольд, А; Жумадилов, К (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
This article provides an overview of the work on the study of radon concentration in the air of residential and office premises, open air, water and soil. The urgency of the issue of internal exposure of the population from natural sources of ionizing radiation is noted. Knowledge of radon concentration is essential in assessing individual exposure doses and compiling the radiation characteristics of the residential premises of the population, especially in areas with a high content of uranium radionuclides. This will make it possible to assess the medical consequences and to carry out a complex of measures in time to prevent exposure of the public to excess levels.